The Influence of Brand Experience and Brand Attitude on Repurchase Intention with Brand Equity as a Mediating Variable on Iphone Users in Aceh (International Journal of Scientific Research and Management (IJSRM), 2024)
This study aims to examine the Brand Experience (B-Experience) and Brand Attitude (B-Attitude) effect on Repurchase Intention (Repurchase-Int) with Brand Equity (B-Equity) as a mediating variable. The population was all users of Apple iPhone products in Banda Aceh City. Determination of the number of samples for Structural Equation Modeling (SEM) analysis using the formula 10 times the number of indicator variables totaling 22 indicators used which amounted to 220 samples. The results showed B-Experience and B-Attitude have a direct effect on B-Equity; B-Experience, B-Attitude, and B-Equity have a direct effect on Repurchase-Int; and B-Equity partially mediates the effect of B-Experience and B-Attitude on Repurchase-Int. These findings all explain that the model tested in this research is accepted, meaning that everything is following research expectations and becomes the premise for future research that wants to develop a theory related to the variables in the model.